Drosophila mitochondrial transcription factor B2 regulates mitochondrial DNA copy number and transcription in Schneider cells. - Matsushima, Y.; Garesse, R.; Kaguni, L.S. (Journal of Biological Chemistry, 2004)
We report the cloning and molecular analysis of Drosophila mitochondrial transcription factor B2 (d-mt-TFB2), a protein that plays a role in mitochondrial transcription and mitochondrial DNA (mtDNA) replication in Drosophila. An RNA interference (RNAi) construct was designed that reduces expression of d-mtTFB2 to 5% of its normal level in Schneider cells. RNAi knock-down of d-mtTFB2 reduces the abundance of specific mitochondrial RNA transcripts 2- to 8-fold and decreases the copy number of mtDNA approximately 3-fold. In a corollary manner, we find that overexpression of d-mtTFB2 increases both the abundance of mitochondrial RNA transcripts and the copy number of mtDNA. In a comparative experiment, we find that overexpression of Drosophila mitochondrial transcription factor A (d-TFAM) increases mtDNA copy number with no significant effect on mitochondrial transcripts. This argues for a direct role for mtTFB2 in mitochondrial transcription and suggests that, if TFAM serves a role in transcription, its endogenous level limits mtDNA copy number but not transcription. Furthermore, we suggest that mtTFB2 increases mtDNA copy number by increasing the frequency of initiation of DNA replication, whereas TFAM serves to stabilize and package mtDNA in mitochondrial nucleoids. Our work represents the first study to document the function of mtTFB2 in vivo, establishing a dual role in regulation of both transcription and replication, and provides a benchmark for comparative biochemical studies in various animal systems.